SARS-CoV-2 Detection and COVID-19 Diagnosis: A Bird’s Eye View - Alzahrani, Abdullah R.; Jabeen, Qaiser; Shahid, Imran; Al-Ghamdi, Saeed S.; Shahzad, Naiyer; Rehman, Sidra; Algarni, Alanood S.; Bamagous, Ghazi A.; AlanazI, Ibrahim Mufadhi M.; Ibrahim, Ibrahim A. A. (Reviews on Recent Clinical Trials, 2023)
The battle against severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) associated coronavirus disease 2019 (COVID-19) is continued worldwide by administering firsttime emergency authorized novel mRNA-based and conventional vector-antigen-based anti- COVID-19 vaccines to prevent further transmission of the virus as well as to reduce the severe respiratory complications of the infection in infected individuals. However; the emergence of numerous SARS-CoV-2 variants is of concern, and the identification of certain breakthrough and reinfection cases in vaccinated individuals as well as new cases soaring in some low-to-middle income countries (LMICs) and even in some resource-replete nations have raised concerns that only vaccine jabs would not be sufficient to control and vanquishing the pandemic. Lack of screening for asymptomatic COVID-19-infected subjects and inefficient management of diagnosed COVID-19 infections also pose some concerns and the need to fill the gaps among policies and strategies to reduce the pandemic in hospitals, healthcare services, and the general community. For this purpose, the development and deployment of rapid screening and diagnostic procedures are prerequisites in premises with high infection rates as well as to screen mass unaffected COVID-19 populations. Novel methods of variant identification and genome surveillance studies would be an asset to minimize virus transmission and infection severity. The proposition of this pragmatic review explores current paradigms for the screening of SARS-CoV-2 variants, identification, and diagnosis of COVID-19 infection, and insights into the late-stage development of new methods to better understand virus super spread variants and genome surveillance studies to predict pandemic trajectories.
Keywords: SARS-CoV-2 detection